PENGEMBANGAN MODUL KOMPOS TERINTEGRASI KONSEP KIMIA SEBAGAI BAHAN AJAR UNTUK SISWA PROGRAM AGRIBISNIS TANAMAN PERKEBUNAN (ATP) SMKN ACEH TIMUR - Jofrishal Jofrishal (Chimica Didactica Acta, 2013)
Learning curriculum in a vocational school combines the adaptive, normative and productive subject group. The adaptive, normative and productive subject groups are expected to be mutually supportive and complementary, in fact the group of subjects did not support each other. The purpose of this study is to develop a learning module for productive subject package (composting techniques) which is integrated by the concept of chemistry as one of the adaptive subjects in vocational school, another purpose of this study is to collect the responses of teachers and students on the module, the module quality assessment by experts, assessment of the portion of chemical concepts that integrated in the module by specialists and module effectivity test. The development of module is using the one of instructional development model in teaching materials development known as ADDIE model (analysis, design, development, implementation, evaluation). The results showed that 92% of teachers responded positively to the module, 85% of students responded positively . While the negative resposes from teacher wes 8% and 15% for student responses. The module quality assessment indicate score 3.36 which the criteria "good" and the expert assessment of chemical concepts are integrated in the module is 70% - 80%. The effectivity of module using student test results indicate the average grades is 92 which criteria "very good". The results suggest that the effectivity of the module is very good for learning.